LEVEL AND SIGNIFICANCE OF C-REACTIVE PROTEIN IN PERSONS WITH METABOLIC SYNDROME - Miljković, Dušan (Medicinski časopis, 2021)
Summary Aim. Previous research has shown that CRP levels are elevated in people with metabolic syndrome (MS) and that low-intensity inflammation is characteristic of MS. The aim was to examine the level and significance of serum CRP in individuals with MS.Methods. The study included 149 outpatients, 67 with MS (68.9 ± 8.7) and 82 without MS (68.9 ± 8.6) as controls (p> 0.05). CRP was determined by turbidimetry with normal values ​​up to 5.0 mg / L.Results. The average CRP level of subjects with MS was 5.33 ± 3.6 mg / L, and without MS 2.46 ± 2.03 mg / L (p 0.05). CRP levels higher than 5.0 mg / L were present in 29.8%  subjects with MS and 6.1% without MS (p
Keywords: Key words: metabolic